Reduced Plasma Nonesterified Fatty Acid Levels and the Advent of an Acute Lung Injury in Mice after Intravenous or Enteral Oleic Acid Administration - Cassiano Felippe Gonçalves de Albuquerque; Patrícia Burth; Mauricio Younes Ibrahim; Diogo Gomes Garcia; Patrícia Torres Bozza; Hugo Caire Castro Faria Neto; Mauro Velho Castro Faria (Mediators of Inflammation)
Although exerting valuable functions in living organisms, nonesterified fatty acids (NEFAs) can be toxic to cells. Increased blood concentration of oleic acid (OLA) and other fatty acids is detected in many pathological conditions. In sepsis and leptospirosis, high plasma levels of NEFA and low albumin concentrations are correlated to the disease severity. Surprisingly, 24 h after intravenous or intragastric administration of OLA, main NEFA levels (OLA inclusive) were dose dependently decreased. However, lung injury was detected in intravenously treated mice, and highest dose killed all mice. When administered by the enteral route, OLA was not toxic in any tested conditions. Results indicate that OLA has important regulatory properties on fatty acid metabolism, possibly lowering circulating fatty acid through activation of peroxisome proliferator-activated receptors. The significant reduction in blood NEFA levels detected after OLA enteral administration can contribute to the already known health benefits brought about by unsaturated-fatty-acid-enriched diets.